Neonate Born to a Mother with a Diagnosis of Suspected Intra-Amniotic Infection versus COVID-19 or Both - Rishi Lumba; Juan Remon; Moi Louie; Michelle Quan; Sourabh Verma; Mona Rigaud; Bgee Kunjumon (Case Reports in Pediatrics)
A diagnosis of intra-amniotic infection is typically made based on clinical criteria, including maternal intrapartum fever and one or more of the following: maternal leukocytosis, purulent cervical drainage, or fetal tachycardia. The diagnosis can also be made in patients with an isolated fever of 39°C, or greater, without any other clinical risk factors present. Coronavirus disease 2019 (COVID-19), caused by the virus SARS-CoV-2, has been noted to have varying signs and symptoms over the course of the disease including fever, cough, fatigue, anorexia, shortness of breath, sputum production, and myalgia. In this report, we detail a case of a newborn born to a mother with a clinical diagnosis of intra-amniotic infection with maternal fever and fetal tachycardia, who was then found to be SARS-CoV-2 positive on testing. Due to the varying presentation of COVID-19, this case illustrates the low threshold needed to test mothers for SARS-CoV-2 in order to prevent horizontal transmission to neonates and to healthcare providers.